Dielectric, ferroelectric and magnetoelectric properties of in-situ synthesized CoFe2O4/BaTiO3 composite ceramics. Issue 7 (May 2020) - Wang, Zhenhua; Gao, Rongli; Chen, Gang; Deng, Xiaoling; Cai, Wei; Fu, Chunlin
Abstract: Magnetoelectric composite materials have attracted more and more attention because of their coupling of ferroelectricity and ferromagnetism. It is a hotspot to realize the combination of ferromagnetic phase and ferroelectric phase. In this work, we used a new strategy to prepare CoFe2 O4 /BaTiO3 composite ceramics: firstly, porous ferromagnetic CoFe2 O4 phase was prepared by annealing of MOFs (metal organic frameworks) precursor Fe3 [Co(CN)6 ]2 . And then, the ferroelectric BaTiO3 phase in-situ grew in the pores of CoFe2 O4 by a hydrothermal method. In the end, the CoFe2 O4 /BaTiO3 composite ceramics sintered at different temperatures have been synthesized. The effects of sintering temperature on the structure, dielectric and ferroelectric properties have also been studied. Because the crystallinity and density increase with the increase of sintering temperature, the composite ceramic sintered at 1200 °C shows the best dielectric properties. It is found that sintering temperature has little effect on the ferroelectric and magnetic properties of ceramics. Taking the CoFe2 O4 /BaTiO3 composite ceramic sintered at 1200 °C as an example, derived from the interaction between the ferromagnetic CoFe2 O4 phase and ferroelectric BaTiO3 phase, the applied magnetic field lead to the reduction of P r and E c .